Question
G136 b (10) -7a-(-2a+4b)= (11) 3a-(b+5a)= (12) (3a+2)-(-a+5)= (13) (a-2b)-(2a+3c)= (14) (-3b+2c)-(-2a+5b)= (15) (4x-7y+z)+(-4x-7y+3z) (16) (4x-7y+z)-(-4x-7y+3z) (17) (a-2b)+(-2a+3b-5c)= (18) (a-2b)-(-2a+3b-5c)=
Solution
4.2
(288 Votes)
Leah
Elite ยท Tutor for 8 years
Answer
### (10)
### (11)
### (12)
### (13)
### (14)
### (15)
### (16)
### (17)
### (18)
Explanation
## Step 1: Distribute the negative sign### Distribute the negative sign to the terms inside the parentheses.## Step 2: Combine like terms### Combine the terms with the same variables.## Step 3: Simplify the expression### Simplify the expression by performing the addition or subtraction.